Analytical modeling nanoparticles‐fines reactive transport in porous media saturated with mobile immiscible fluids. Issue 10 (27th June 2019) - Yuan, Bin; Moghanloo, Rouzbeh G.
Abstract: This work develops a new analytical solution for the reactive flow of aqueous nanofluid into porous media originally saturated with a mobile aqueous suspension containing fine particles and a mobile oleic‐phase. The enhancement of nanoparticles on fines attachment onto rock grains is modeled through the increase of the maximum retention capacity of rock grains. Implementing the splitting technique and stream‐function converts the original 3 × 3 system of partial‐differential equations into 2 × 2 sub‐system of nanoparticles‐fines reactive transport, and a lifting equation where only phase saturation appears. Then, method of characteristics is applied to achieve the analytical solution, the validity of which is tested by numerical simulation. The historical profiles of suspended/adsorbed nanoparticles, suspended/attached fines, and phase saturation along 1‐D porous medium are reproduced. The impact of injected nanoparticles concentration and carrier fluid saturation on fines attachment is investigated. This work provides a simple‐yet‐rigorous approach to evaluate nanofluid injection to control fines migration in multiphase flow.